A combined day-ahead and intraday optimal scheduling strategy considering a joint frequency regulation reserve scheme among wind, photovoltaic, and thermal power - Zhu, Shulin; Wang, Haiyun; Wang, Weiqing; Chang, Xiqiang (Frontiers in Energy Research, 2023)
Under the premise of setting a certain reserve power for frequency regulation, the new energy power plant (NEPP) transformed by frequency regulation control can participate in the system frequency regulation. Considering the cooperation problem of reserve power for frequency regulation between multiple NEPPs, a joint frequency regulation reserve scheme among wind, photovoltaic and thermal power is designed this paper. The group of NEPPs composed of all NEPPs in the system works in the state of dynamic stepped output derating, and participates in the system frequency regulation together with thermal power units. On the basis of the joint frequency regulation reserve scheme, considering that the accuracy of new energy forecast will directly affect the frequency regulation effect of NEPPs, a combined day-ahead and intraday scheduling strategy considering the joint frequency regulation reserve scheme is proposed, and the relevant scheduling model is derived. The improved IEEE RTS 24 system is used as the test system to calculate. The results of the calculations show that the proposed strategy can optimize the participation scheme of frequency regulation of new energy, reduce the power and economic losses of new energy caused by the participation in frequency regulation, and improve the ability of power system to accommodate the output power of new energy under the premise of ensuring that the steady-state frequency deviation does not exceed the allowable frequency limits.